2005
DOI: 10.1111/j.1075-122x.2005.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Conservative Treatment in Idiopathic Granulomatous Mastitis

Abstract: Idiopathic granulomatous mastitis (IGM) is a rare benign inflammatory disease of the breast that mimics carcinoma of the breast. Its etiology and treatment remain unclear. A retrospective review of nine women with histopathologic diagnosis of IGM was performed. The women had a mean follow-up of 18.7 months and a mean age of 45.7 years (range 32-83 years). The main presentation was breast mass (100%). Clinically and radiologically, 55.6% of the women were suspected to have malignancy. One patient was treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
232
1
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(257 citation statements)
references
References 13 publications
9
232
1
15
Order By: Relevance
“…Several studies have shown varying degrees of success with all of these methods. Furthermore, management is complicated by a high rate of recurrence (16-50%) (9)(10)(11).…”
mentioning
confidence: 99%
“…Several studies have shown varying degrees of success with all of these methods. Furthermore, management is complicated by a high rate of recurrence (16-50%) (9)(10)(11).…”
mentioning
confidence: 99%
“…FNA cytologic diagnosis can lead to misdiagnosis of tuberculosis or carcinoma Tse et al (2003). There is neutrophylic infiltration in the field and a lot of granulomatous histiocytes but definite diagnosis can be achieved through biopsy or excisional biopsy and the result of histopathology (Lai et al, 2005;Verfaillie et al, 2006;Malycha, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In the relapsed cases supplementary therapeutic treatment is advised. Taghizadeh et al (2007) and Akcan et al (2006) other appropriate choices are as following: oral steroid therapy with a dose of 16 mg daily for 6 weeks and gradual tapering and surgical approach in the relapsed cases (Azlina et al, 2003;Hirata et al, 2003) waiting and conservative approach with short interval follow-up periods (Lai et al, 2005;Diesing et al, 2004) and finally using Metothrexate and Colchicine in cases resistant to corticotherapy. Diesing et al (2004) and Kim et al (2003) it is essential to ruled out infectious causes in corticotherapy cases and antibiotic treatment should start before administration of oral steroid in abscess cases.…”
Section: Resultsmentioning
confidence: 99%
“…%25 olguda lezyon bilateraldir ve %25 hastada ağrı ve hassasiyet mevcuttur. Lai ve arkadaşları İLGM tanılı 100 hastanın 56'sında meme karsinomu klinik ön tanısının varlığını bildirmektedirler (7)(8)(9)(10). Bazen malignite benzeri klinik ve radyolojik bulgularla seyreden hastalığa şüpheli ince iğne aspirasyon biyopsisi sonuçları da eklenebilir.…”
Section: Olguunclassified